АДМІНІСТРАТИВНО-ПРАВОВІ ФОРМИ ЗАПОБІГАННЯ ТА ПРОТИДІЇ ЗЛОЧИННОСТІ ОРГАНАМИ ДЕРЖАВНОЇ МИТНОЇ СЛУЖБИ УКРАЇНИ - Черкасський, Руслан Анатолійович (SUPREMANCE OF LAW, 2016)
The article, based on the analysis of scientific views of scientists and current legislation of Ukraine, identifies and characterizes the following administrative and legal forms of combating and preventing crime by the State Customs Service: planning the work of the LCA in the study area; prevention and cessation of offenses in the customs sphere; taking organizational measures to prevent and combat crime. It is established that administrative and legal forms of prevention and counteraction to crime by the State Customs Service of Ukraine should be interpreted as based on current legislation, defi ned by the tasks set before this central executive body, functions, as well as competence, set of government actions and procedures. implemented by this agency and its representatives in the field of combating and preventing crime.
Keywords: administrative and legal forms; counteraction and prevention of crime; State Customs Service